An Assessment Of Twitter Effectiveness On Increasing Trust In E-Commerce In Saudi Arabia - Alqammash, Fahad Ali (Archives of Business Research, 2018)
Social media has been widely used by businesses and integrated with E-commerce solutions in order to increase two—way interaction between customers and businesses as well as to increase transparency and trust. Twitter and Facebook are two platforms whereby businesses are able to better understand the needs and wants of the customers and as a means for customers to be able to relate better to the businesses. While previous studies have identified factors impacting trust in e-commerce, social commerce has not been considered. Given its prevalence and its use in enhancing customer perceptions about trust, this study aims to explore social media (Twitter and Facebook) adoption by small and medium scale e-businesses in the Kingdom. Using a mixed methods approach, the study analyses to what extent Twitter and Facebook participation has improved trust thereby impacting revenue. The study analyses how customers are able to better relate to the brand because of social commerce integration.